\(\widetilde{g}\)-Open Sets in Fuzzy Topological Spaces - Balasubramaniyan, K.; Prabhakaran, R. (Communications in Mathematics and Applications, 2023)
New category of fuzzy generalized closed sets, specifically fuzzy \(\widetilde{g}\)-closed sets is to launch and argue of fuzzy topological spaces. Further, compare with related to various types of fuzzy generalized closed sets are investigated. Moreover, the properties of fuzzy \(\widetilde{g}\)-closed sets are given of this paper.